2021
DOI: 10.1097/md.0000000000025428
|View full text |Cite
|
Sign up to set email alerts
|

The changing patterns of comorbidities associated with human immunodeficiency virus infection, a longitudinal retrospective cohort study of Medicare patients

Abstract: The objective of this paper is to determine the temporal trend of the association of 66 comorbidities with human immunodeficiency virus (HIV) infection status among Medicare beneficiaries from 2000 through 2016. We harvested patient level encounter claims from a 17-year long 100% sample of Medicare records. We used the chronic conditions warehouse comorbidity flags to determine HIV infection status and presence of comorbidities. We prepared 1 data set per year for analysis. Our 17 study data sets ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Hypertension, diabetes mellitus, and depression or mood disorders were the most frequently reported comorbidities in our study. In previous epidemiological studies conducted among PLWH in the United States, many of these comorbid conditions were also reported, underscoring the relevance of understanding and managing HIV and its consequences (Gallant et al, 2017;Williams et al, 2021). Similar to our results, another study reported that frailty among older PLWH is characterized by hypertension, diabetes mellitus, hyperlipidemia, and polypharmacy, all of which may result in metabolic syndrome (McMillan et al, 2020).…”
Section: Depressive Symptoms and Comorbiditiessupporting
confidence: 90%
“…Hypertension, diabetes mellitus, and depression or mood disorders were the most frequently reported comorbidities in our study. In previous epidemiological studies conducted among PLWH in the United States, many of these comorbid conditions were also reported, underscoring the relevance of understanding and managing HIV and its consequences (Gallant et al, 2017;Williams et al, 2021). Similar to our results, another study reported that frailty among older PLWH is characterized by hypertension, diabetes mellitus, hyperlipidemia, and polypharmacy, all of which may result in metabolic syndrome (McMillan et al, 2020).…”
Section: Depressive Symptoms and Comorbiditiessupporting
confidence: 90%
“…PWH are at increased risk for metabolic dysfunction and disease [ 3 5 ]. It is therefore important that we improve our understanding of the etiology of these comorbidities to reduce morbidity and mortality in this population [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The life expectancy of people with HIV (PWH) has increased considerably due to the development of effective antiretroviral therapy (ART) over the past several decades [ 1 , 2 ]. However, PWH are at increased risk for several chronic, noninfectious comorbidities including obesity, dyslipidemia, diabetes mellitus, and cardiovascular disease [ 3 5 ]. As a result, metabolic and cardiovascular diseases are now some of the leading causes of death among PWH in developed countries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…PLHIV have greater risk for various mental and physical comorbidities in addition to conditions discussed in the current study [ 44 , 45 ] and are more likely to engage in polypharmacy [ 46 ]. Therefore, this subpopulation may have unique differential effects of tobacco cessation on improvements in co-occurring conditions.…”
Section: Discussionmentioning
confidence: 99%